Nursing and Nursing in the Service of the Patient and their Importance - Nahla Faisal Mohamed Arif, Salha Mahdi Mubarak Al Harqan, Sahar Mahdi Mubarak Al Hargan, Ahood Khadeir G Damna, Shreefa Sluman S Al Yami, Areej Saeed Jaman Alfarhan Alyami; Saada Mahdei Mubarak Al Horgan, Kefaya Hussein Alhassanah, Huda Marzook Mubrook Arrehan, and Nouf Musead Eid Al Najrani, Reem Ibrahim Abdullah Al-Doosary (Journal of International Crisis and Risk Communication Research, 2024)
The title of this article might at first seem like a bit of an exaggeration, and indeed it is, but no more so than the time-honored real estate mantra: location, location, location. Those in the real estate business have learned firsthand that although other factors have some influence on consumer preference, in the end, they pale in comparison with the impact of one factor in particular—property location. Similarly, those with first-hand experience in the field of healthcare realize that there are a host of factors that play a role in determining patient satisfaction; however, when all is said and done, it is the influence of nursing services that has by far the most significant impact. Most staff nurses have a general understanding of this importance, but many have a less than full appreciation of just how strong it is. Even more importantly, hospital boards, medical staffs, senior management, and nursing leadership need to have a clear understanding of this relationship since there is now pm ample evidence that as staff nurse job satisfaction goes, so goes patient satisfaction. This important association has proven to be direct, pervasive, and consistent over time. 1 2n response to increasing pressures to contain healthcare costs, hospital restructuring initiatives have become relatively commonplace, •as have associated efforts to reduce nurse staffing levels.3'4 At the same time, there has been a growing emphasis on improving patient satisfaction, particularly now that it has become a factor in determining levels Of Medicare reimburse— ment. In the absence Of a thorough appreciation Of the extent Of the role staff nurses play in determlning patient satisfaction, premature and/or excessive reductions in nurse staffing levels will result in unintended, penny—wise—pound-foolish outcomes.